9.1k views
13 votes
Help me pleasee. Solve the system by substitution

Help me pleasee. Solve the system by substitution-example-1

1 Answer

4 votes

Answer:

(3, - 2 )

Explanation:

Given the 2 equations

4x - 2y = 16 → (1)

y = - 5x + 13 → (2)

Substitute y = - 5x + 13 into (1)

4x - 2(- 5x + 13) = 16 ← distribute and simplify left side

4x + 10x - 26 = 16

14x - 26 = 16 ( add 26 to both sides )

14x = 42 ( divide both sides by 14 )

x = 3

Substitute x = 3 into (2) for corresponding value of y

y = - 5(3) + 13 = - 15 + 13 = - 2

solution is (3, - 2 )

User JStephen
by
4.8k points